Hubungan Tingkat Pengetahuan dengan Kepatuhan Minum Obat ARV di Ruang Khusus CST Puskesmas Kemayoran Jakarta - Donny Prastyo; Rahayu Winarti; Menik Kustriyani (Malahayati Nursing Journal, 2026)
ABSTRACT HIV/AIDS continues to be one of the leading global health challenges. Antiretroviral therapy (ART) has proven effective in reducing viral load, yet its success largely depends on patient adherence. Knowledge is often considered an important factor influencing adherence, although previous research has shown inconsistent results. "The purpose of this study is to determine the relationship between the level of knowledge and adherence to antiretroviral (ARV) medication among patients in the CST (Care, Support and Treatment) unit at Kemayoran Public Health Center, Jakarta, in 2025. This study applied a quantitative correlational design involving 51 HIV-positive patients undergoing ART at the CST Unit of Kemayoran Public Health Center, Jakarta. Data were collected using the ART Knowledge Scale – Honghe Prefecture and the MMAS-8 questionnaire. Statistical analysis was performed using the Spearman Rank correlation test. The findings indicated that the majority of respondents demonstrated a low level of knowledge (64.7%), while adherence levels were mostly moderate (39.2%) and high (39.2%). Statistical analysis yielded a p-value of 0.723 (p 0.05) with a correlation coefficient of r = 0.051, suggesting no significant relationship between knowledge and adherence. Knowledge alone is not the main determinant of adherence to ART. Other factors, including patient motivation, family support, and psychosocial conditions, appear to play a more substantial role in influencing treatment adherence. Keywords: HIV/AIDS, Knowledge, Compliance, Antiretroviral Therapy (ART), Kemayoran Community Health Center.  ABSTRAK Latar Belakang, sampai saat ini HIV/AIDS menjadi masalah kesehatan global yang utama. Terapi antiretroviral (ARV) terbukti efektif menekan jumlah virus, namun keberhasilannya sangat dipengaruhi kepatuhan pasien. Pengetahuan dianggap sebagai faktor penting dalam kepatuhan, meskipun hasil penelitian sebelumnya tidak konsisten. Tujuan penelitian ini untuk mengetahui hubungan antara tingkat pengetahuan dengan kepatuhan mengonsumsi obat antiretroviral (ARV) di ruang khusus CST (Care, Support and Treatment) Puskesmas Kemayoran Jakarta Tahun 2025.Metode penelitian ini menggunakan desain kuantitatif korelasional terhadap 51 responden pasien HIV yang menjalani ART di ruang CST Puskesmas Kemayoran Jakarta. Data dikumpulkan menggunakan kuesioner ART Knowledge Scale – Honghe Prefecture dan MMAS-8. Proses analisis statistik menggunakan uji Rank Spearman. Hasil penelitian menunjukkan bahwa sebagian responden memiliki tingkat pengetahuan rendah (64,7%) dengan tingkat kepatuhan sedang (39,2%) maupun tinggi (39,2%). Hasil uji statistik mendapatkan nilai p = 0,723 (p 0,05) dengan koefisien korelasi r = 0,051, yang menunjukkan tidak ada hubungan signifikan antara pengetahuan dan kepatuhan. Kesimpulan,pengetahuan tidak tidak menjadi penentu utama dalam kepatuhan minum obat ARV. Faktor-faktor lainnya seperti motivasi pasien, dukungan keluarga, dan kondisi psikososial dianggap lebih berpengaruh terhadapa kepatuhan pasien. Kata Kunci: HIV/AIDS, Pengetahuan, Kepatuhan, Antiretroviral Therapy (ART), Puskesmas Kemayoran.